3D printed plastics for beam modulation in proton therapy. (18th May 2015) - Lindsay, C; Kumlin, J; Jirasek, A; Lee, R; Martinez, D M; Schaffer, P; Hoehr, C
Abstract: Two 3D printing methods, fused filament fabrication (FFF) and PolyJet™ (PJ) were investigated for suitability in clinical proton therapy (PT) energy modulation. Measurements of printing precision, printed density and mean stopping power are presented. FFF is found to be accurate to 0.1 mm, to contain a void fraction of 13% due to air pockets and to have a mean stopping power dependent on geometry. PJ was found to print accurate to 0.05 mm, with a material density and mean stopping power consistent with solid poly(methyl methacrylate) (PMMA). Both FFF and PJ were found to print significant, sporadic defects associated with sharp edges on the order of 0.2 mm. Site standard PT modulator wheels were printed using both methods. Measured depth-dose profiles with a 74 MeV beam show poor agreement between PMMA and printed FFF wheels. PJ printed wheel depth-dose agreed with PMMA within 1% of treatment dose except for a distal falloff discrepancy of 0.5 mm.